Extracorporeal shock waves down-regulate the expression of interleukin-10 and tumor necrosis factor-alpha in osteoarthritic chondrocytes - Moretti, Biagio (BioMed Central, 2008)
BACKGROUND: The purpose of this study was to investigate the effects of extra corporeal shock waves (ESW) therapy on the metabolism of healthy and osteoarthritic human chondrocytes, and particularly on the expression of IL-10, TNF-alpha and beta1 integrin. METHODS: Human adult articular cartilage was obtained from 9 patients (6 male and 3 females), with primary knee osteoarthritis (OA), undergoing total joint replacement and from 3 young healthy donors (HD) (2 males, 1 female) with joint traumatic fracture. After isolation, chondrocytes underwent ESW treatment (electromagnetic generator system, MINILITH SL1, STORZ MEDICAL) at different parameters of impulses, energy levels and energy flux density. After that, chondrocytes were cultured in 24-well plate in DMEM supplemented with 10% FCS for 48 hours and then beta(1 )integrin surface expression and intracellular IL-10 and TNF-alpha levels were evaluated by flow-cytometry. RESULTS: At baseline, osteoarthritic chondrocytes expressed significantly lower levels of beta1 integrin and higher levels and IL-10 and TNF-alpha levels. Following ESW application, while beta1 integrin expression remain unchanged, a significant decrease of IL-10 and TNF-alpha intracellular levels was observed both in osteoarthritic and healthy chondrocytes. IL-10 levels decreased at any impulses and energy levels, while a significant reduction of TNF-alpha was mainly found at middle energies. CONCLUSION: Our study confirmed that osteoarthritic chondrocytes express low beta(1 )integrin and high TNF-alpha and IL-10 levels. Nonetheless, ESW treatment application down-regulate the intracellular levels of TNF-alpha and IL-10 by chondrocytes, suggesting that ESW might restore TNF-alpha and IL-10 production by osteoarthritic chondrocytes at normal levels. However, further in vivo and in vitro studies are necessary to establish if ESW can represent a viable option in the treatment of OA.